Comparative Study of the Physicochemical Characterization and Quality of Edible Vegetable Oils - ICHU C.B.; NWAKANMA H.O. (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The comparative study of physicochemical characterization and quality of edible vegetable oils was done in this work using standard analytical techniques. These oils include: Elaeis guineensis jacquin (palm oil), Glycine max (L.)Merr. (soybean oil),Cocus nucifera (coconut oil), Arachis hypogaea L.(groundnut oil), Olea europaea (Olive oil), Sesamum indicum. L. (sesame seed oil),Brassica campestris L. (mustard seed oil), and palm kernel oil (PKO). The range of the values obtained are as follows: saponification value (SV): 5.58 - 249.90 mgKOH/g, peroxide value (PV): 0.45 -290.00 mEqO2/kg of sample, acid value (AV): 0.34 - 68.88 mgKOH/g, iodine value (IV): 0.45 - 16.37g I2/100g sample, density (Ds): 908.9 - 919.6kg/m3, viscosity (Vs): 20.58– 77.97 mm2/sec, specific gravity (SG): 0.9089- 0.9196, and refractive index (RI): 1.4578 – 1.4773. The studied characteristics of the oil samples in most cases compared favorably with; FAO/WHO (CODEX Alimentarius) values. There were some observed levels of significant differences in the values at p≤0.05. The data also showed that the oil quality is good and edible inferring from their low AV. Their IV values which were inconsistent with standard values may have been affected by storage conditions and exposure to air and light. On the other hand, their low PV serves as indicators of the presence or high levels of anti-oxidants in the oils. The result of the work confirms these edible oils to be of good quality